(untitled) - O’Brien, James A. (New York, 2010)
O'Brien's "Introduction to Information Systems, 15/e" reflects the contemporary use of enterprise-wide business systems. New real-world case studies continue to correspond with this industry reality. The text's focus is on teaching the future manager the potential effect on business of the most current IT technologies such as the Internet, Intranets, and Extranets for enterprise collaboration, and how IT contributes to competitive advantage, reengineering business processes, problem solving, and decision-making.
Keywords: Management information systems,Management,Electronic commerce,Kinh doanh,Hệ thống quản lý thông tin,Thương mại điện tử,Quản lý,Business; Data processing,Xử lý dữ liệu,Xử lý thông tin,Data processing